Financial leverage and performance: the case of financial technology firms. Issue 44 (20th September 2021) - Papadimitri, Panagiota; Pasiouras, Fotios; Tasiou, Menelaos
ABSTRACT: Over the past years, the financial technology industry has gained considerable attention from policy makers and regulators, market participants, as well as the general public. Despite the interest of these stakeholders, academic research on the topic is scarce and we aim to extend the literature by examining the impact of financial leverage on the performance of FinTech firms. Using a sample of 146 U.S. FinTech firms operating in ten market segments over the period 2000–2016, we find that financial leverage has a negative impact on profitability and risk-adjusted performance. We also reveal that the magnitude of the influence of leverage depends on firm age. The results are robust to the use of a cross-country sample, alternative model specifications and estimation approaches.